Time in the documentary theater An applied study on the play "Samar Party for the 5th of June" by Saadallah Wannos - بوش, فخري; الحسن المصريّ, حسن صالح (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Time is directly related to the life and consciousness of the individual since ancient times. He senses this connection through his living in a world that is constantly changing around him, and this main feature of the dramatic time in the documentary theater that assesses its dialectic and its impact with the recipient, and connects the present time that is shaped by the dramatic event and your love Dramatic text and historical time fused in the present time. The time in the documentary theater is going from the beginning to the end, passing through the center through spiral, circular or horizontal structures that intersect with the living time.